In vivo active-targeting fluorescence molecular imaging with adaptive background fluorescence subtraction - Vega, Jorge D.; Hara, Daiki; Schmidt, Ryder M.; Abuhaija, Marwan B.; Tao, Wensi; Dogan, Nesrin; Pollack, Alan; Ford, John C.; Shi, Junwei (Frontiers in Oncology, 2023)
Fluorescence molecular imaging enables highly sensitive and specific tumor detection based on active targeting nanoparticles. For in vivo breast tumor targeted imaging, the fluorescent poly lactic-co-glycolic acid (PLGA) nanoparticle conjugated with anti- epidermal growth factor receptor (EGFR) was implemented. This PLGA-anti-EGFR nanoparticle demonstrated high tumor-specific uptake and enhanced tumor detection capabilities. Nevertheless, there still existed considerable background fluorescence induced by the nonspecific uptake of nanoparticles in healthy organs, which complicated the tumor detection. We developed an algorithm that estimated the background fluorescence from the measured distribution of excitation light transmitting through tissues. Furthermore, an adaptive strategy was implemented to selectively refine the background fluorescence subtraction. First, an in vivo experiment was performed on a mouse intratumorally injected with fluorescent nanoparticles, to validate the reliability of the proposed method in a stringent situation wherein the target fluorescence was overlapped with the strong background. Then, we conducted in vivo studies on 10 mice which were inoculated with orthotopic breast tumors and intravenously injected with PLGA-anti-EGFR nanoparticles. Results demonstrated that active targeting nanoparticles combined with the adaptive background fluorescence subtraction increased the accuracy of fluorescence molecular imaging, affording sensitive tumor detection.